Physicochemical Factors Affecting the Growth of Burkholderia pseudomallei in Soil Microcosm - Wang-ngarm, Supunnipa (The American Society of Tropical Medicine and Hygiene, 2014)
Burkholderia pseudomallei causes melioidosis, the third most common cause of death from infectious diseases in northeast Thailand. Four physicochemical factors were set so that their values covered the range of the northeast, which is an endemic area. The soil pH was set at pH 4–10, soil salinity was 0.0–5.0% NaCl, total iron was 50–150 mg/kg soil, and carbon to nitrogen ratio (C/N) was 10:1 to 40:1. The experiments were carried out at 37°C, and soil moisture was maintained for 7 days. The number of viable bacterial cells was counted daily. Soil pH, salinity, Fe, and C/N ratio affected the bacterial growth. The bacterial colony was significantly (P < 0.05) reduced at soil pH > 8, soil salinity > 1% NaCl, and C/N ratio > 40:1. However, the growth of B. pseudomallei was enhanced by increasing the concentrations of iron significantly (P < 0.05). We propose using these findings to control B. pseudomallei in situ.